STRATEGI PENGELOLAAN HUTAN BERKELANJUTAN - Arif Dwi Cahyono, Sujianto, Febri Yuliani (Universitas Riau, 2019)
Sustainable Forest Management Strategy. The purpose of this study was to find out the strategies for sustainable forest management of forest management units (KPH) on the Kampar Peninsula. This type of research is qualitative. The research informants were UPTD KPH TBS staff and KPH observers from NGOs. Data collection techniques are interviews, observation and documentation. Data analysis through stages, starting from data reduction, data classification and drawing conclusions. The results of the study indicate that the program being implemented has not been well planned.